2002
DOI: 10.1073/pnas.172514599
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of α-synuclein null mice to the parkinsonian neurotoxin MPTP

Abstract: Parkinson's disease (PD) is most commonly a sporadic illness, and is characterized by degeneration of substantia nigra dopamine (DA) neurons and abnormal cytoplasmic aggregates of ␣-synuclein. Rarely, PD may be caused by missense mutations in ␣-synuclein. MPTP, a neurotoxin that inhibits mitochondrial complex I, is a prototype for an environmental cause of PD because it produces a pattern of DA neurodegeneration that closely resembles the neuropathology of PD. Here we show that ␣-synuclein null mice display st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
391
0
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(428 citation statements)
references
References 34 publications
26
391
0
11
Order By: Relevance
“…MPTP, a known selective dopaminergic neurotoxin that inhibits mitochondrial complex I activity (as mentionedabove) creates an oxidative stress environment that enhances alphaͲsyn aggregation and consequent death of dopaminergic neurons [176]. Moreover, Dauer and colleagues [179] investigated the toxic effect of MPTP in mice lacking SNCA gene and concluded that these animals were resistant to MPTP, giving support to alphaͲsyn critical role in the pathogenesis of toxinͲinduced dopaminergic neuron death. A recent study performed by Kalivendi et al [180] demonstrated that oxidantͲinduced alternative splicing of alphaͲsyn plays a crucial role in the mechanism of dopamineneuron cell death, contributing to PD.…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…MPTP, a known selective dopaminergic neurotoxin that inhibits mitochondrial complex I activity (as mentionedabove) creates an oxidative stress environment that enhances alphaͲsyn aggregation and consequent death of dopaminergic neurons [176]. Moreover, Dauer and colleagues [179] investigated the toxic effect of MPTP in mice lacking SNCA gene and concluded that these animals were resistant to MPTP, giving support to alphaͲsyn critical role in the pathogenesis of toxinͲinduced dopaminergic neuron death. A recent study performed by Kalivendi et al [180] demonstrated that oxidantͲinduced alternative splicing of alphaͲsyn plays a crucial role in the mechanism of dopamineneuron cell death, contributing to PD.…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…Four lines of ␣-SYN KO mice have been demonstrated to be resistant to the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, which is a mitochondrial inhibitor relatively selective for the nigrostriatal DA system (11,66,67), and the protective effect appeared to be upstream of the mitochondria (66).…”
Section: ␣-Syn a Major Component Of Lbmentioning
confidence: 99%
“…Transgenic mice expressing mutant or wildtype α-syn show motor deficits, alterations in dopamine levels, and α-syn-positive inclusions (Hashimoto et al, 2003;Maries et al, 2003). Alpha-syn is also involved in the action of neurotoxins, such as MPTP and rotenone, used to model PD (Dauer et al, 2002;Betarbet et al, 2000).…”
Section: Introductionmentioning
confidence: 99%